If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x = 60x Solving 23x = 60x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60x' to each side of the equation. 23x + -60x = 60x + -60x Combine like terms: 23x + -60x = -37x -37x = 60x + -60x Combine like terms: 60x + -60x = 0 -37x = 0 Divide each side by '-37'. x = 0 Simplifying x = 0
| 5(4-2k)-4K=90 | | 6xy-7xy+8x+3=-6y+6 | | 4.8-9.6x= | | 4.50+2.25n=31.50 | | y=3.1x-0.1 | | -5c+4=4 | | -x-3+x=2x-7 | | (1n-8)-(-2+2)= | | -2-6(6b+5)=-248 | | 30+0.25x=59.5 | | 7-4w= | | 3(2+y)-4v=v+16 | | 4(8p-3)= | | -3+15=-3t+5t | | 30.00+0.25x=59.5 | | 7x=4x+50 | | 20+3(2+5c)= | | 14x+8= | | y=1.7x-5.4 | | 5(6v-2)=-70 | | 3z+8=6z+7 | | -8+4x=6x+2x | | -9u-17=-2[u-2] | | -9(3n+6)=31 | | -2.8-(-9.3)= | | 25=7+13-4s | | (2-1k)-3(-4K+2)= | | 12x+36=-8x+4 | | 8v+v=8v+7 | | 10+44+a=2a | | -41s=7 | | 3a=3 |